2021
DOI: 10.1016/j.intimp.2020.107172
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Egg Yolk Antibodies (IgYs) block the binding of multiple SARS-CoV-2 spike protein variants to human ACE2

Abstract: The SARS-CoV-2 virus is still spreading worldwide, and there is an urgent need to effectively prevent and control this pandemic. This study evaluated the potential efficacy of Egg Yolk Antibodies (IgY) as a neutralizing agent against the SARS-CoV-2. We investigated the neutralizing effect of anti-spike-S1 IgYs on the SARS-CoV-2 pseudovirus, as well as its inhibitory effect on the binding of the coronavirus spike protein mutants to human ACE2. Our results show that the anti-Spike-S1 IgYs showed significant neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Although the great potential of chicken IgY for COVID‐19 has been proposed by several labs (Lu et al, 2020 ; Shen et al, 2021 ; Wei et al, 2021 ), to our knowledge, the affinity of IgY to antigens has not been reported yet. Most current anti‐SARS‐CoV‐2 antibodies neutralize viruses by binding to epitopes on the S protein of SARS‐CoV‐2 (Tai et al, 2020 ; Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the great potential of chicken IgY for COVID‐19 has been proposed by several labs (Lu et al, 2020 ; Shen et al, 2021 ; Wei et al, 2021 ), to our knowledge, the affinity of IgY to antigens has not been reported yet. Most current anti‐SARS‐CoV‐2 antibodies neutralize viruses by binding to epitopes on the S protein of SARS‐CoV‐2 (Tai et al, 2020 ; Tian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…Till now, several studies have been carried out on the potential anti‐SARS‐CoV‐2 effect of IgY (Lu et al, 2020 ; Shen et al, 2021 ; Wei et al, 2021 ). IgY targeting the full‐length S protein, S1 subunit or RBD were produced, and all studies showed a high titer and variable neutralizing activity against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasal antibody prophylaxis is an especially effective means against multiple viral pathogens ( 29 32 ). Further, key characteristics of the mechanism of action of anti-SARS- CoV-2 IgY may be ideal for effective transient immunization while awaiting global COVID-19 vaccination: a) anti-spike-S1 IgY can neutralize or bind SARS-CoV-2 in vitro ( 33 35 ), b) superficially administered anti-SARS-CoV-2 IgY may bind to the spike protein on the surface of the virus, competing with the binding of the viral spike protein to the human angiotensin-converting enzyme 2 receptor to prevent cell entry and infection, c) anti-SARS-CoV-2 IgY may also agglutinate SARS-CoV-2 on the surface of the mucosa, thus preventing viral lateral motility and entry across the mucosa, and d) intranasal administration can deliver anti-SARS-CoV-2 IgY to the nasal passage and throat mucosa (through mucociliary clearance), the main routes of viral entry and replication. This approach may be especially valuable for immediate and short-lived protection in health care and other at-risk service workers in regions where new variants of SARS-CoV-2 may evade immunity produced by vaccines or where COVID-19 vaccination is unavailable.…”
Section: Diagnosis and Treatment Of Viral Infectionsmentioning
confidence: 99%
“…It is currently used as an antigen for serological test kits, and as an immunogen. RBD could be used to produce neutralizing antibodies at large scale in animal systems such as egg yolk (IgY) 13,14 or in horses 15 .…”
Section: Introductionmentioning
confidence: 99%